The y-intercept:
y=(0)^2+2(0)-3
y=-3
(0,-3)
The x-intercepts:
0=x^2+2x-3
0=(x+3)(x-1)
x=-3 and 1
(1,0) and (-3,0)
2006-12-11 03:17:04
·
answer #1
·
answered by Anonymous
·
4⤊
0⤋
To find x intercept, make y = 0
So, x^2+2x-3 = 0
x^2+2 = 3
so, x = 1 or -3
To find y intercept, make x = 0
So, y = -3
You got the answer, (1 and -3) and (-3,-3)
2006-12-11 10:18:17
·
answer #2
·
answered by Avtaar 3
·
1⤊
0⤋
when y=0 x=-3 and x=1
when x=0 y=-3
2006-12-11 10:16:08
·
answer #3
·
answered by photojenny 2
·
1⤊
0⤋
Solving quadratic equation we get:
X=1,-3
thus it cuts X axis at 1,-3
it cuts y axis at x= -3
2006-12-11 10:14:14
·
answer #4
·
answered by Som™ 6
·
1⤊
0⤋
when y=0,
x^2+2x-3 = 0
x^2+3x-x-3=0
x(x+3)-1(x+3)=0
x=1 or x=-3
when x=0,
y= -3
(1, -3) or (-3, -3)
2006-12-11 10:13:54
·
answer #5
·
answered by Babygirl 3
·
1⤊
0⤋